Sex Offender Recidivism: Some Lessons Learned From Over 70 Years of Research - Lussier, Patrick (Criminal justice review, 2024)
Sex offender recidivism (SOR) has been the subject of research for over 70 years. Myths, misconceptions, and erroneous conclusions about SOR, however, remain widespread, impeding the development of evidence-based policies aimed at preventing sexual offenses. To address the rich but uneven literature, a comprehensive review was conducted making it possible to provide a contextualized overview of scientific knowledge against the backdrop of methodological issues, challenges, and shortcomings. Over the years, researchers have been asked to provide a simple answer to a seemingly simple question: what are the recidivism rates for sexual offending? In response, the field has produced a wide range of findings making it difficult to draw firm conclusions, leaving room for interpretation and personal biases. The variations in recidivism rates are attributable to offender and methodological characteristics, both of which are embedded in a particular sociolegal context. As a result, the base rate of SOR is more effectively considered in terms of a series of questions that should include the type of recidivism, with whom, over what period, and in what context. Issues and debates that have marked the field and fueled its growth are highlighted. Research innovations and important areas of research are also discussed.